Determinants of poor self-rated health among adults in urban Mozambique - Boaventura M. Cau; Joana Falcão; Carlos Arnaldo (BMC, 2016)
Abstract Background Self-rated health is a measure expressing the general condition of health of individuals. Self-rated health studies are common in developed countries and in some developing regions. Despite increasing proportion of adult and older population in sub-Saharan Africa and poor population health indicators, there is a dearth of studies on self-rated health in the region. This study examines factors associated with poor self-rated health among adult individuals in Maputo metropolitan area in Mozambique. Methods Data for this study come from a survey of 1768 individuals aged 18 years or more carried out in Maputo metropolitan area, Mozambique, in 2015. Employing multiple logistic regression, the study used a subsample of 677 female and male respondents aged 40 years or more to estimate the determinants of poor self-rated health. Results About 54 % of respondents aged 40 years or more believed that their health status was poor. Female respondents [Odds Ratios (OR) = 3.43, p <0.01], single (OR = 4.71, p < 0.05), widow (OR = 1.81, p < 0.05), separated or divorced (OR = 2.08, p < 0.05) and those believing that hypertension or heart problem was a major community health problem (OR = 1.56, p < 0.05) displayed higher odds of reporting poor health than their peers, net of other factors. Furthermore, individuals aged 40-49 years (OR = 0.45, p < 0.01), or 50-59 years (OR = 0.59, p < 0.05), those whose work involves intensive physical activity (OR = 0.60, p < 0.05) and those from households treating drinking water (OR = 0.49, p < 0.01) showed lower odds of reporting poor health, adjusting for other factors. Conclusion Overall, the results point to the importance of age, gender, marital status, socioeconomic circumstances, individuals' health behaviors and perceived community health problems as key determinants of poor self-rated health among adults in Maputo metropolitan area. Given the growing number of adult and older people in sub-Saharan Africa, the rising importance of non-communicable diseases and the scarcity of studies on determinants of poor self-rated health among adults in the region, our findings may have implications for a better understanding of the drivers of poor health among adults in urban sub-Saharan Africa